Bundelakhaṇḍa darśana : prākrtika, dhārmika, paurāṇika, sāṃskrtika, bhaugolika, aitihāsika, rājanaitika, sāhityika, śaikshaṇika, kalātmaka, ārthika, audyogika paramparāoṃ kā pratīka - Tripāṭhī, Motī Lāla, 1922- (Lakshamī Prakāśana ;, 1980)
Land and people of Bundelkhand region, Central India; a sociohistorical study.